2021
DOI: 10.1093/geroni/igab054
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship Between Preference for Solitude and Subjective Well-Being Among Japanese Older Adults

Abstract: Background and Objectives Focusing on the fact that older adults with positive emotions tend to spend time alone, this study aimed to examine the relationship between preference for solitude and subjective well-being among older adults. In Study 1, we developed a revised version of the Preference for Solitude Scale with a three-factor structure, unlike the single-factor structure of the original scale. In Study 2, we examined the relationship between preference for solitude and subjective wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Toyoshima and Kusumi (2022) [ 42 ] examined the relationship between preference for solitude (which in this study refers to time spent alone) and subjective well-being and reported that enjoyment of solitude and productivity while being solitary were associated with the maintenance of subjective well-being among the elderly. In our study, the number of individuals with high levels of social isolation who were intentionally socially isolated or enjoyed solitude was unclear; however, it could be inferred that there was a certain number of them.…”
Section: Discussionmentioning
confidence: 99%
“…Toyoshima and Kusumi (2022) [ 42 ] examined the relationship between preference for solitude (which in this study refers to time spent alone) and subjective well-being and reported that enjoyment of solitude and productivity while being solitary were associated with the maintenance of subjective well-being among the elderly. In our study, the number of individuals with high levels of social isolation who were intentionally socially isolated or enjoyed solitude was unclear; however, it could be inferred that there was a certain number of them.…”
Section: Discussionmentioning
confidence: 99%
“…Affinity for solitude shares conceptual overlap with other similar constructs, including preference for solitude (Burger, 1995), unsociability (Coplan & Weeks, 2010), and intrinsically motivated solitude (Nguyen et al, 2018). Whereas these concepts vary to different extents on the consideration of the motivational and behavioral features, affinity for solitude, which may be used interchangeably with enjoyment of solitude (Cramer & Lake, 1998; Toyoshima & Kusumi, 2022), focuses more on the emotional experience of time spent alone (e.g., Borg & Willoughby, 2022; Daly & Willoughby, 2020; Hu et al, 2022).…”
Section: Affinity For Solitude and Adjustment In Chinese Contextmentioning
confidence: 99%
“…Moreover, we aim to investigate the correlates of preference for solitude among the general adult population in Germany. Such knowledge can enrich our understanding of individual differences in social behavior, which is important because a greater preference for solitude may have consequences for well-being (which can be either positive or negative, depending on the outcome [ 12 ]) and mental health outcomes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%